Pengaruh Gaya Belajar dan Kemampuan Berhitung Dasar terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas IV SDN se Gugus RA Kartini Kabupaten Pati - Ilya Ni'matuzzahro; Noening Andrijati (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This study aims to: 1) Examine the influence of learning styles on students' problem-solving abilities in mathematics, 2) Investigate the effect of basic calculation skills on mathematical problem-solving abilities, and 3) Obtain information on the combined effect of both independent variables on the dependent variable. This research employs a quantitative approach with a correlational design (ex post facto). The population and sample consist of all fourth-grade students from SDN in the Gugus RA Kartini, Kabupaten Pati, totaling 99 students. Data collection techniques include tests, interviews, questionnaires, observations, and documentation. Data analysis is conducted through prerequisite analysis and final data analysis. Based on the research findings, it can be said that: 1) Learning styles have a big impact on students' ability to solve mathematical problems; 2) Basic calculation skills have a big impact on students' ability to solve mathematical problems; 3) Students' ability to solve mathematical problems is significantly impacted by both learning methods and fundamental calculating capabilities with a contribution of variables X1 and X2 to Y of 55.9%.The results align with existing theories that learning styles and basic calculation skills impact students' mathematical problem-solving abilities. Future research is expected to further develop this study by exploring other factors related to students' mathematical problem-solving skills.